2022
DOI: 10.5543/khd.2021.85619
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Adjustment to Cardiovascular Diseases and Spiritual Well-Being in Iranian Patients

Abstract: Objective: In this study, we assessed psychosocial adjustment in patients with cardiovascular diseases and its relationship with spiritual well-being.Methods: This descriptive analytic study was performed in 2018 in Qazvin, Iran. The subjects were 150 patients who were admitted to the cardiac ward of a teaching hospital. Data were collected using a background variables checklist developed by the researchers and two standard questionnaires of Psychosocial Adjustment to Illness Scale and Ellison-Paloutzian Spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…In the present study, women had higher spiritual health than men, consistent with previous studies conducted in Iran and other countries [ 39 40 ]. There is still considerable debate about the reasons for these gender differences.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, women had higher spiritual health than men, consistent with previous studies conducted in Iran and other countries [ 39 40 ]. There is still considerable debate about the reasons for these gender differences.…”
Section: Discussionsupporting
confidence: 92%
“…Existing data confirm higher smoking prevalence in Iranian men than women [38] and could justify the higher CVD risk score among male participants of the current study. In the present study, women had higher spiritual health than men, consistent with previous studies conducted in Iran and other countries [39,40]. There is still considerable debate about the reasons for these gender differences.…”
Section: Discussionsupporting
confidence: 92%
“…In Akın and Durna's study, the area of family environment was found to be affected in single patients (12). (13). The findings were interpreted as social responsibilities that marriage brings in our country may affect psychosocial adjustment.…”
Section: Discussionmentioning
confidence: 93%